Che's afterlife the legacy of an image - Casey, Michael 1967- (Vintage Books, 2009)
Casey, Buenos Aires bureau chief for Dow Jones Newswires, examines intellectual property and iconography through the lens of the famous image of Che Guevara captured by fashion photographer Alberto Korda. The author does not neglect the relevant biographical details or history, but his focus is Che as a brand. He wants to understand why the Korda image remains so compelling to such a wide variety of people and how it continues to represent so many different (and differing) causes; he suggests that the power of Che, the brand, is in its ability to be anything to anyone.